Lingual Alveolar Soft Part Sarcoma in a 1-Year-Old Infant: Youngest Reported Case With Characteristic ASPSCR1-TFE3 Fusion. (July 2019) - Ruffle, Amy; Cameron, Malcolm; Jonas, Nicolaas; Levine, Samantha; Mills, Caroline; Hook, C Elizabeth; Murray, Matthew J
Alveolar soft part sarcoma (ASPS) is an exceptionally rare non-rhabdomyosarcomatous soft tissue sarcoma (NRSTS), characterized by the translocation t(X;17) p(11.2;q25). This translocation results in the chimeric ASPSCR1-TFE3 transcription factor which drives tumorigenesis. Complete surgical resection is crucial in allowing a successful outcome in these cases. Here, we describe an 11-month-old female infant who presented with a well-circumscribed lesion of the tongue, with the clinical and radiologic appearances of an infantile hemangioma. This led to an initial plan for surveillance management. However, the mass continued to enlarge and the lesion was therefore biopsied when the infant was 17 months old. Histology showed plump epithelioid tumor cells, in many places lining pseudoalveolar spaces. Occasional Pas-D inclusions were present in the cytoplasm. Immunostaining showed nuclear positivity for TFE-3. Real-time quantitative polymerase chain reaction testing confirmed the presence of ASPSCR1-TFE3 fusion transcripts, characteristic of the translocation t(X;17) p(11.2;q25) observed in ASPS. This represents the youngest reported ASPS case with a confirmed molecular diagnosis. Complete surgical resection was undertaken and a surveillance imaging schedule implemented. This case highlights the need for regular review of the initial diagnosis and the importance of multidisciplinary discussion and early biopsy where the clinical course does not follow that expected for the putative (nonhistologically confirmed) diagnosis.